The digital financial revolution in China - Dollar, David; Huang, Yiping, 1964- (Brookings Institution Press, 2022)
"Describing how China is in the lead in transforming finance for the digital ageChina has been at the forefront of one of the most important revolutions in contemporary business practices: the rapid growth of digital finance. From mobile payments to online investment, from Big Tech lending to digital insurance, and from open banking to central bank digital currency, China has been among the most advanced--sometimes the most advanced--of the major economies in adopting technologies that are changing both the financial system and the lives of millions of people. China has been especially far-sighted in promoting financial inclusion--offering financial services for the first time to people regardless of their location, job status, or income. This book is the product of a joint research project between economists at the National School of Development, especially the affiliated Institute of Digital Finance, at Peking University and at the Brookings Institution. It investigates the impact of financial technology on job creation, income distribution, and consumer welfare in China. It also examines larger systemic issues such as monetary policy, stability of the banking sector, and international trade and payments. With a primary focus on the development of digital finance in China, most of the contributions are from Chinese economists. But the volume also considers implications for the rest of the world in several chapters written by international economists from Brookings. The depth and breadth of the descriptions and analysis in this ground-breaking book will appeal to scholars of China, finance professionals, and policymakers around the globe."--